Asuhan Keperawatan pada Tn. S dengan Post Operasi Hernioraphy pada Hernia Inguinalis Lateralis Dextra di Ruang Mawar 2 RSUD dr. Soeselo Kabupaten Tegal - Khikmatul Khoeriyah; Ahmad Zakiudin; Sukirno Sukirno (Jurnal Anestesi, 2024)
A hernia is a protrusion or protusion of the contents of a cavity through a defect or weak part of the abdominal wall. A hernia consists of a ring, a sac and the contents of the hernia. The occurrence of a hernia is triggered by an increase in intra-abdominal pressure that is repeated or continuous (Sayuti, et al., 2023). The purpose of this paper is to find out and provide nursing care to Mr. S with post-operative hernioraphy on the right lateral inguinal hernia in the mawar 2 ward of dr. Soeselo Hospital, Tegal Regency according to nursing standards. The method used is the data collection method in the form of interviews, observations and examinations. From the case review, it was found that the client’s main complaint was pain in the surgical wound, P: pain when moving, Q: like being pulled, R: upper right groin, S: 6, T: continuous pain. The nursing problems found were acute pain, impaired physical mobility and knowledge deficit. Interventions were arranged based on the theory in SDKI, SLKI and SIKI as well as on the client’s condition and could be implemented.